Surface Modification of Microfiltration Polypropylene Membrane for Molecular Air Filtration - A.A.I.A.S Komaladewi; PTP Aryanti; I D G Ary Subagia; I W Surata; I G Wenten (International Journal of Engineering and Emerging Technology, 2019)
Microfiltration polypropylene (MPP) membrane has increasingly been used in separation processes due to its good chemical and mechanical stability, high selectivity to submicron particles, and low cost. In this paper, the MPP membrane was modified by coating the surface with a composite polysulfone (PSf)/PEG400/ZnO layer. Then, the modified MPP membrane was used for fine particle removal from air. Performance of modified MPP membrane as a function of polymer and ZnO nanoparticles (ZnO-NPs) concentration in coating solution, and coating time, was investigated. The SEM image showed that the presence of ZnO-NPs in polymer solution generated macrovoids in the coating layer. Permeate flux decreased with increasing polymer and ZnO-NPs concentration, but the flux increased with increasing coating time. Meanwhile, fine particle removal efficiency increased with the increase of operating pressure. A stable air flux of 19 L m-2 h-1 was obtained at ZnO-NPs concentration of 3 wt.%. The removal efficiency of PM1, PM2.5, and PM10 at operating pressure of 2 bar were 70%, 74%, and 70%, respectively.